2021
DOI: 10.1002/ecs2.3430
|View full text |Cite
|
Sign up to set email alerts
|

Cascading effects: insights from the U.S. Long Term Ecological Research Network

Abstract: Ecosystems across the United States are changing in complex and unpredictable ways and v www.esajournals.org 1 May 2021 v Volume 12(5) v Article e03430mussels, and harmful algal blooms. Collectively, these stories highlight the need for long-term studies to sort out the complexities of different types of ecological cascades. The diversity of sites within the LTER network facilitates the emergence of overarching concepts about trophic interactions as an important driver of ecosystem structure, function, service… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 128 publications
0
3
0
Order By: Relevance
“…Latitudinal changes in NAP phytoplankton biomass have been recorded and attributed to regional climate patterns reflected by a progressive warming towards the southern end of the Peninsula, with increasing chlorophyll‐ a in that sector, contrasting with trends recorded northwards (Brown et al, 2019; Montes‐Hugo et al, 2009). Moreover, these changes in phytoplankton biomass have been followed by shifts in community composition, particularly resulting in a smaller fraction of large diatoms in the northern sector (Bahlai et al, 2021; Brown et al, 2019; Montes‐Hugo et al, 2009; Schofield et al, 2010). In the NAP region, specifically, several studies have reported an increasing contribution of small cryptophytes to the phytoplankton community composition (e.g., Mendes et al, 2013; Mendes, Tavano, Dotto, et al, 2018; Mendes, Tavano, Kerr, et al, 2018), with our decadal in situ dataset suggesting a niche segregation between cryptophytes and diatoms based on physical and chemical properties of the water‐column (Figure S2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Latitudinal changes in NAP phytoplankton biomass have been recorded and attributed to regional climate patterns reflected by a progressive warming towards the southern end of the Peninsula, with increasing chlorophyll‐ a in that sector, contrasting with trends recorded northwards (Brown et al, 2019; Montes‐Hugo et al, 2009). Moreover, these changes in phytoplankton biomass have been followed by shifts in community composition, particularly resulting in a smaller fraction of large diatoms in the northern sector (Bahlai et al, 2021; Brown et al, 2019; Montes‐Hugo et al, 2009; Schofield et al, 2010). In the NAP region, specifically, several studies have reported an increasing contribution of small cryptophytes to the phytoplankton community composition (e.g., Mendes et al, 2013; Mendes, Tavano, Dotto, et al, 2018; Mendes, Tavano, Kerr, et al, 2018), with our decadal in situ dataset suggesting a niche segregation between cryptophytes and diatoms based on physical and chemical properties of the water‐column (Figure S2).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, these changes in phytoplankton biomass have been followed by shifts in community composition, particularly resulting in a smaller fraction of large diatoms in the northern sector (Bahlai et al, 2021;Brown et al, 2019;Montes-Hugo et al, 2009;Schofield et al, 2010). In the NAP region, specifically, several studies have reported an increasing contribution of small cryptophytes to the phytoplankton community composition (e.g., Mendes et al, 2013;, with our decadal in situ dataset suggesting a niche segregation between cryptophytes and diatoms based on physical and chemical properties of the water-column (Figure S2).…”
Section: The Distribution Dominance Patterns and Niche Preferences Of...mentioning
confidence: 99%
“…Lady beetles contribute broadly to biological control as predators of key arthropod pests (Obrycki and Kring 1998, Evans 2009, Weber and Lundgren 2009, Rondoni et al 2021), but the introduction and establishment of exotic lady beetle species threaten native species and the long-term resilience of this ecosystem service (Bahlai et al 2021). Following their establishment and spread within North America, the exotic species H. axyridis and C. septempunctata have become dominant within many native lady beetle communities (Alyokhin and Sewell 2004, Harmon et al 2007, Bahlai, Colunga-Garcia, et al 2015, Gardiner et al 2021).…”
Section: Discussionmentioning
confidence: 99%